A new class of Dengue and west Nile virus protease inhibitors with submicromolar activity in reporter gene DENV-2 protease and viral replication assays - Kühl, Nikos; Graf, Dominik Korbinian; Bock, Josephine; Behnam, Mira A. M.; Leuthold, Mila; Klein, Christian D. (Journal of medicinal chemistry, 2020)
Dengue and West Nile virus are rapidly spreading global pathogens for which no specific therapeutic treatments are available. One of the promising targets for drug discovery against dengue and other flaviviruses is the viral serine protease NS2B-NS3. We present the design, synthesis, and in vitro and cellular characterization of a novel chemotype of potent small-molecule non-peptidic dengue protease inhibitors derived from 4-benzyloxyphenylglycine. A newly developed luciferase-based DENV-2 protease reporter system in HeLa cells (DENV2proHeLa) was employed to determine the activity of the compounds in a cellular environment. Specificity and selectivity of the DENV2proHeLa system were confirmed by viral titer reduction assays. The compounds reach low micromolar to upper nanomolar inhibitory potency in cell-based assays, are selective against other serine proteases, and do not show relevant cytotoxicity. An extensive structure-activity relationship study provides a perspective for further drug development against flaviviral infections.
Gesehen am 24.09.2020